STUDI KUALITATIF TENTANG KOLABORASI KELUARGA DAN MASYARAKAT DALAM MENUNJANG PENDIDIKAN DASAR DI SDN 1 TEPUNG SARI - Wulandari, Ayu; Kuswidyanarko, Arief; Riyanti, Henni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The success of basic education cannot rely solely on the school institution, but rather requires an integrated ecosystem with families and the social environment. This study aims to analyze in depth the dynamics, concrete forms, and obstacles in collaboration between schools, families, and the community in supporting basic education at SDN 1. Using a descriptive qualitative approach with a case study design, data were collected through in-depth interviews with the principal, teachers, committee members, and parents, reinforced by participatory observation and documentation studies. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study revealed three main findings: first, school-family collaboration is still dominated by digital communication (WhatsApp groups), which is effective for remedial learning but is not optimal in terms of strategic program involvement; second, the community, through the school committee, contributes significantly as "social capital" in overcoming limitations in physical budgets and moral supervision; third, structural barriers in the form of parents' economic busyness and cultural barriers in the form of the conventional perception that "education is the absolute responsibility of the school" remain the main limitations. This study concludes that strengthening partnership literacy for parents is urgently needed to shift the form of collaboration from merely administrative to participatory-strategic.